2013
DOI: 10.1080/10934529.2013.730425
|View full text |Cite
|
Sign up to set email alerts
|

The immobilization ofArthrospira platensisbiomass in different matrices—A practical application for lead biosorption

Abstract: The biosorption of lead by cyanobacteria (Arthrospira platensis) immobilized in different matrices was studied. This was the first time that sodium alginate, silica gel and agarose beads have been used for the removal of lead from solutions of the metal in concentrations ranging from 50 to 500 mg/L. The effect of pH in the range 4.0 to 5.5 on lead removal was also investigated. For the best biosorbent chosen from those mentioned above, lead biosorption in samples of real wastewater was examined. The maximum bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…According to Chen and Pan ( 2005a ) who carried out the research involving living cells of Arthrospira platensis , the biomass removed lead from solutions at concentrations below 10 mg/l. Moreover, in our previous study (Duda-Chodak et al 2013 ), we successfully conducted biosorption at higher lead concentrations by engaging immobilised cyanobacterium biomass and at the same time we demonstrated that free cells of Arthrospira platensis survived for at least 24 h in solutions containing up to 100 mg Pb/l regardless the pH of solutions. Therefore, we decided to continue the research involving living cells of A. platensis for lead biosorption.…”
Section: Introductionsupporting
confidence: 51%
“…According to Chen and Pan ( 2005a ) who carried out the research involving living cells of Arthrospira platensis , the biomass removed lead from solutions at concentrations below 10 mg/l. Moreover, in our previous study (Duda-Chodak et al 2013 ), we successfully conducted biosorption at higher lead concentrations by engaging immobilised cyanobacterium biomass and at the same time we demonstrated that free cells of Arthrospira platensis survived for at least 24 h in solutions containing up to 100 mg Pb/l regardless the pH of solutions. Therefore, we decided to continue the research involving living cells of A. platensis for lead biosorption.…”
Section: Introductionsupporting
confidence: 51%
“…This results in destabilization of the structure, leading to leakage of algal cells (Hertzberg and Jensen 1989 ). To avoid this problem, the Spirulina medium was replaced by distilled water, such as in the case of the alginate-entrapped cells of S. platensis used in biosorption processes (Duda-Chodak et al 2013 ). The structure of the matrixes was stable; however, the release of photosynthetic pigments was observed, indicating cell damage.…”
Section: Discussionmentioning
confidence: 99%